Sistem Informasi Pembelian Dan Penjualan Barang Bekas Berbasis Java Desktop Pada Toko Besi Tua Samin - Marwan M. Londol (Jurnal Ilmiah Sistem Manajemen Informatika dan Komputerisasi Akuntansi, 2021)
The process of collecting data on the purchase and sale of used goods at the Samin scrap metal shop is currently still done manually, that is, every purchase and sale transaction is recorded in a transaction book. Recording and calculating manually is an ineffective and efficient job, because data collection or calculation errors can occur which result in losses. The research method in this study uses a qualitative method approach. Sources of qualitative data were obtained through observation and interviews as well as literature studies related to the theories that support the process of preparing Minor Papers. The results obtained in the study, namely, the system can manage goods data, purchase and sales data and can process purchase and sales notes. With this information system for buying and selling used goods, it is hoped that it can help Samin iron shop in managing sales and purchase data.